Reaction, diffusion and dissociation of excitons on carbon nanotubes - Allam, J; Sutton, R; Sajjad, M; Litvinenko, K; Wang, Z; Siddique, S; Yang, Q; Brown, T; Loh, W (2010)
Photoexcitation of carbon nanotubes generates excitons which decay by exciton-exciton annihilation at sufficient density. We examine this decay under conditions of one, few and many excitons per nanotube. A classic ID reaction-diffusion behaviour is observed, with decay limited by diffusion for t>3ps and by reaction for t<3ps. At high densities the exciton population saturates, and by analysis of the rate equations we show that this is consistent with dissociation of excitons when their spacing is 1.3nm, close to the exciton length. ©2010 Optical Society of America.